2023
DOI: 10.1038/s41598-023-32085-7
|View full text |Cite
|
Sign up to set email alerts
|

Etiological analysis of patients with sudden sensorineural hearing loss: a prospective case–control study

Abstract: Sudden sensorineural hearing loss (SSNHL) is a multifactorial emergency disease. Until now, the etiology of SSNHL is still unknown. Previous studies regarding the etiology of SSNHL are clinical studies depending on clinical data collection and analysis. Due to the insufficient sample size or various selective bias in clinical studies, the results of these studies may be inaccurate. This prospective case–control study aimed at exploring the possible etiology and risk factors of SSNHL. We enrolled 255 SSNHL pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
2
0
1
Order By: Relevance
“… 6 7 8 22 Several studies have found high NLR and PLR values to be associated with a worse prognosis in neuro-otological diseases including Bell’s palsy and sudden sensorineural hearing loss. 23 24 25 Although NLR has been considered an inflammatory biomarker in peripheral vertigo, the usefulness of this parameter as a prognostic predictor remains inconclusive in AUV. 9 10 11 12 13 14 15 16 One study found a significant relationship between NLR and the clinical severity of AUV, but those authors evaluated the disease severity using the duration of subjective dizziness requiring antivertigo drugs, rather than using an objective questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“… 6 7 8 22 Several studies have found high NLR and PLR values to be associated with a worse prognosis in neuro-otological diseases including Bell’s palsy and sudden sensorineural hearing loss. 23 24 25 Although NLR has been considered an inflammatory biomarker in peripheral vertigo, the usefulness of this parameter as a prognostic predictor remains inconclusive in AUV. 9 10 11 12 13 14 15 16 One study found a significant relationship between NLR and the clinical severity of AUV, but those authors evaluated the disease severity using the duration of subjective dizziness requiring antivertigo drugs, rather than using an objective questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular dysfunction and viral infection are considered to be the most common causes of ISSNHL. It was reported that vascular damage could increase blood viscosity, make the blood in a hypercoagulable state, cause microcirculation disorders in the inner ear, and lead to damage to cochlear hair cells, and ultrastructural changes ( 5 ). Viruses, such as the herpes simplex virus, varicella-zoster virus, mumps, cytomegalovirus, and rubella, have been considered to correlate with the pathogenesis of ISSNHL.…”
Section: Discussionmentioning
confidence: 99%
“…Although several etiologies of ISSNHL, such as viral infection, inflammation, inner ear circulation disorders, cochlear membrane breaks, and vascular occlusion, have been suggested, the exact pathogenesis is still unclear ( 3 , 5 ). Due to the anatomical proximity of the cochlea and vestibule, ISSNHL is frequently accompanied by vestibular dysfunction ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cholesterol levels were higher in patients with SSNHL compared to controls, but no significant associations were found for smoking, HDL, LDL, triglyceride, or BMI [8]. In contrast, two studies found no association between SSNHL and comorbidities such as hypertension and diabetes, as well as smoking and drinking habits [9,10] or hyperlipidemia [10]. Alternatively, one study found higher levels of leukocytes, neutrophils, neutrophil-tolymphocyte ratio, and fibrinogen in patients with SSNHL [9].…”
Section: Comorbity Associationmentioning
confidence: 92%
“…In contrast, two studies found no association between SSNHL and comorbidities such as hypertension and diabetes, as well as smoking and drinking habits [9,10] or hyperlipidemia [10]. Alternatively, one study found higher levels of leukocytes, neutrophils, neutrophil-tolymphocyte ratio, and fibrinogen in patients with SSNHL [9].…”
Section: Comorbity Associationmentioning
confidence: 94%